PENERAPAN OFFICE AUTOMATION DALAM MENINGKATKAN EFISIENSI ADMINISTRASI PEMERINTAHAN: STUDI LITERATURE REVIEW PADA SISTEM SATU KEMENKEU - Fricilia, Chatrine (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The digital transformation in government administration has become crucial in enhancing public service efficiency. This study examines the implementation of office automation systems in Indonesian government institutions, with a specific focus on the Satu Kemenkeu system at the Ministry of Finance. Through a systematic literature review methodology, this research analyzes strategic aspects of office automation implementation, including organizational readiness, technological infrastructure, change management, and administrative efficiency outcomes. The findings indicate that office automation significantly improves document disposition processes, reducing processing time from days to hours, enhances transparency and accountability, and supports paperless governance initiatives. However, implementation faces challenges including digital literacy gaps, resistance to change, and infrastructure limitations. This study provides strategic recommendations for government agencies planning to implement similar systems, emphasizing the importance of comprehensive change management, continuous training programs, and phased implementation approaches.